2017
DOI: 10.1002/cctc.201601607
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of Foams for Electrocatalysis

Abstract: Developing low cost and efficient anode and cathode materials toward electrocatalysis are regarded as one of the most desirable yet challenging research directions, which are intimately related to the pressing energy, environmental and human health issues. Currently, 3 D foam (such as Ni foam, Cu foam, and graphene foam) based heterogeneous catalysts have been intensively explored for actively catalyzing the electrode reactions. Their inherent characteristics of stereo‐network structure, high specific area and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
133
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(139 citation statements)
references
References 285 publications
(312 reference statements)
2
133
0
2
Order By: Relevance
“…Recently, the design of three‐dimensional (3 D) Co‐based oxygen‐evolving nanoarray catalysts exhibiting high activities under neutral conditions was reported . Despite the high popularity of porous 3 D electrodes in electrochemical energy applications, the authors did not directly or quantitatively analyze the impact of the 3 D structure on the catalytic performance of the Co‐OECs . The reason might be related to the presumption that Co‐OECs are porous enough for efficient proton transport, which has turned out to be true under certain circumstances .…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, the design of three‐dimensional (3 D) Co‐based oxygen‐evolving nanoarray catalysts exhibiting high activities under neutral conditions was reported . Despite the high popularity of porous 3 D electrodes in electrochemical energy applications, the authors did not directly or quantitatively analyze the impact of the 3 D structure on the catalytic performance of the Co‐OECs . The reason might be related to the presumption that Co‐OECs are porous enough for efficient proton transport, which has turned out to be true under certain circumstances .…”
Section: Figuresupporting
confidence: 89%
“…Despite the high popularity of porous 3 D electrodes in electrochemical energy applications, the authors did not directly or quantitatively analyze the impact of the 3 D structure on the catalytic performance of the Co‐OECs . The reason might be related to the presumption that Co‐OECs are porous enough for efficient proton transport, which has turned out to be true under certain circumstances . Although Co‐OECs exhibit volume activity owing to their porous, hydrated structure, recent work revealed that their reaction rates could be much higher at the surface exposed to the electrolyte owing to proton‐transport limitations .…”
Section: Figurementioning
confidence: 99%
“…The high‐performance of 3D NiCo‐Bi/NF electrode can be attributed to several factors: the intrinsically high activity of the NiCo‐Bi nanosheet arrays with the amorphous state and the high valence of the metal acting as active sites during the whole electrolysis; the unique morphology of interconnected NiCo‐Bi nanosheets array on macroporous NF, which enables large working surface area and excellent gas bubble dissipation ability; and the low resistance of the as‐prepared electrode because the catalyst is directly converted from NiCo‐LDH on highly conductive NF, avoiding using chemical binders (such as Nafion) which tends to impede charge transport during catalytic reactions.…”
Section: Figurementioning
confidence: 99%
“…Traditionally, water splitting is an ideal way to mass produce hydrogen, especially in comparison to natural gas reforming. The oxygen evolution reaction (OER), as one of the most formidable tasks in the development of modern electrochemistry, has been identified as the bottleneck of water splitting . The OER suffers from sluggish kinetics arising from proton‐coupled four‐electron transfer and the formation of an oxygen–oxygen bond, which result in a high overpotential that hinders the efficiency of both photon‐driven and electricity‐driven water splitting .…”
Section: Figurementioning
confidence: 99%